Colposcopic evaluation of cervical erosion in symptomatic women - Patil, Pooja; Sharma, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was carried out to find the colposcopic findings in the symptomatic patients with cervical erosion and correlate the findings with cytology and histopathology. Methods: All the patients coming to gynaecological OPD with symptoms of white discharge, pruritus vulvae, menstrual irregularities were examined by per speculum examination and all those who had cervical erosion were included in the study and pap smear and colposcopy both were done in all subjects. The colposcopic guided biopsy was done in women with abnormal findings on colposcopy (50 women) and reports were compared. Abnormal colposcopic findings were graded according to Reid’s colposcopic index (RCI). Results: Majority of patients came with the complaint of white discharge per vaginum (55%).Out of 120 patients, 85 women (70.9%) had inflammatory pap smear and 35 women (29.1%)had abnormal pap smear. All patients underwent colposcopic examination and out of 120 patients, 67(55.8%) showed normal colposcopic findings and 50 women (41.6%) had abnormal colposcopic finding and biopsy was taken. 3 women had unsatisfactory colposcopy. Histopathology confirmed 24 (48%) women with CIN I and 12 (24%) CIN II and 6 (12%) CIN III and 2 (4%) women with carcinoma cervix. The colposcopy findings and histopathology correlated in 88%. Conclusions: Colposcopy should be prescribed to all symptomatic patients with cervical erosion as it is a good diagnostic tool for pre-malignant conditions of cervix and correlates well with histopathological findings.